Idiopathic Peripheral Neuropathy Responsive to Sympathetic Nerve Blockade and Oral Clonidine. (26th August 2012) - Walters, Jenna L.; Lonergan, Daniel F.; Todd, Robert D.; Jackson, Tracy P.
Abstract : A 52-year-old female presented with idiopathic stocking-glove neuropathy. She underwent a series of right and left stellate ganglion blocks with ropivacaine and clonidine, followed by lumbar sympathetic blocks. This resulted in complete symptom relief for two weeks. These procedures were repeated after a two-month interval; at that time she was still experiencing partial relief from the first series. She again remained completely pain free for several weeks following the injections. As the pain partially returned, daily oral clonidine was initiated and resulted in almost complete cessation of her symptoms, which persisted at a three-month follow-up examination.